BS ISO 9735-11. Electronic data interchange for administration, commerce and transport (EDIFACT). Application level syntax rules (Syntax version number: 4, Syntax release number: 1). Part 11. Version 3 compatible profile for Version 4 of ISO 9735 (22nd April 2021) - British Standards Institution,
No abstract available